2023
DOI: 10.3390/w15234045
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics and Antimicrobial Efficacy of Plasma-Activated Water Produced by an Air-Operated Coaxial Dielectric Barrier Discharge Plasma

F. S. Miranda,
V. K. F. Tavares,
M. P. Gomes
et al.

Abstract: In this study, Plasma-Activated Water (PAW) was synthesized using a coaxial Dielectric Barrier Discharge (DBD) reactor, benefiting from the elevated capacity of air-flow-assisted DBD discharges to enhance nitrogen-based species concentration. By manipulating operational parameters, including gas flow rate, activation time, and DI water volume, we achieved significant concentrations of reactive oxygen and nitrogen species (RONS). As a result, the PAW obtained displayed pronounced physicochemical attributes: a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…For gas flow control, an air rotameter (FLDA3215ST, Omega Engineering Inc., Stamford, USA) was employed. Further specifications of the DBD reactor geometry are detailed in [9,13,17].…”
Section: Hybrid Plasma Discharge Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…For gas flow control, an air rotameter (FLDA3215ST, Omega Engineering Inc., Stamford, USA) was employed. Further specifications of the DBD reactor geometry are detailed in [9,13,17].…”
Section: Hybrid Plasma Discharge Setupmentioning
confidence: 99%
“…It has been demonstrated that water treatment using plasma is a promising technique for designing the next generation for tooth-related diseases [5], bacterial inactivation [6], and treatment of cell cancer [7]. PAW production has been reported by different plasma sources such as pin-to-water plasma [8], dielectric barrier discharge (DBD) [9], and gliding arc plasma jet (GAPJ) [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation